Drought induces opposite changes in organ carbon and soil organic carbon to increase resistance on moso bamboo - Ge, Xiaogai; Mao, Yilian; Zhou, Benzhi; Wang, Xiaoming; Li, Mai–He (Frontiers in Plant Science, 2024)
The variety of organs carbon concentration may be important for tree survival rate, drought resistance and tree subsequent recovery. However, it remains unclear how drought affect structural carbohydrate (SC) and non–structural carbohydrate (NSC) export and transport on clonal plant, which can be correlated with sustain physiological metabolism and group drought resistance by resource sharing. To better understand the adaption ability of clone plants to drought and the linkage of organ carbon with soil organic carbon (SOC) fractions, we assessed how long–term drought affect organ carbon and its impact on SOC fractions among moso bamboo (Phyllostachys edulis) ramets. The results showed that there was significant difference on lignin, cellulose: lignin ratio and soluble sugar in leaves and roots (p<0.05) instead of branches (p>0.05). Effect of drought on SC and NSC varied with different organs and ramet age. Drought significantly increased soluble sugar concentration of leaves and roots by 15.5–31.0% and 10.6–24.8% for current-year bamboo. Compared with CK, drought decreased SOC by 6.7–19.1%, microbial biomass carbon (MBC) by 55.3–68.7%, readily oxidizable carbon (ROC) by 11.2–29.8%, particulate organic carbon (POC) by 25.1–47.4% but no effect on mineral–associated organic carbon (MOC). Drought changed the relationships of carbon components between plant organs and soil. In the control treatments, SC of leaves were significantly positively correlated with ROC, NSC of branches were positively correlated with ROC and MBC, NSC of roots were significantly positively correlated with SOC. Overall, our results suggest that drought strengthened the linkage of plant organ carbon and soil carbon cycling among moso bamboo ramets in ecosystem studies, which are critical for predicting tree resistance and management in subtropical forest under drought.